Eletrodinâmica de ordem superior em (2+1)D - Dias, M [UNESP] (2007)
We present in this work a number of results in Poldolsky's formulation of the (2+1) dimensional Electromagnetism. We focus our attention on the nonrelativistic regime of scatterings. We analyse the possibility of existence of bound states for the time-independent Schrödinger equation, by considering the scattering of two bosonic (with and without the Chern-Simons term) and fermionic particles; in the latter case, we also compute finite-temperature corrections. We finally consider the application of the theory to Quantum Electrodynamics, also in (3 + 1) dimensions, and we explicitly work out the renormalization group 'beta' function in this case